PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN APLIKASI SMART APP CREATOR 3 PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Ali, Jihan; Annisa, Annisa; Wasid, Ahmad; Rahmadani, Kurniati; Fricticarani, Ade; Dayurni, Popi (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
The use of learning media is an integral part of the learning method used. This study aims to develop Smart App Creator 3 learning media in Information and Communication Technology subjects. The research method used is the R&D method with data collection techniques through a questionnaire given to 17 class X students of SMK Pasundan 1 Serang City. The results of the study were valid learning media with a value of 0.875. Practicality test of learning media given to 1 teacher and 1 lecturer with an average percentage of 83.6%. While the results obtained from the analysis of practicality by students are an average percentage of 82.35%. So it can be concluded that Smart App Creator 3 learning media is feasible to use as learning media. This research is expected to be a learning media for Information and Communication Technology subjects and can be useful for teachers, students and advanced researchers.